Outcomes of Patients With Hypothyroidism and COVID-19: A Retrospective Cohort Study - van Gerwen, Maaike; Alsen, Mathilda; Little, Christine; Barlow, Joshua; Naymagon, Leonard; Tremblay, Douglas; Sinclair, Catherine F.; Genden, Eric (Frontiers in Endocrinology, 2020)
Coronavirus diseases (COVID-19) is associated with high rates of morbidity and mortality and worse outcomes have been reported for various morbidities. The impact of pre-existing hypothyroidism on COVID-19 outcomes remains unknown. The aim of the present study was to identify a possible association between hypothyroidism and outcomes related to COVID-19 including hospitalization, need for mechanical ventilation, and all-cause mortality. All patients with a laboratory confirmed COVID-19 diagnosis in March 2020 in a large New York City health system were reviewed. Of the 3703 COVID-19 positive patients included in present study, 251 patients (6.8%) had pre-existing hypothyroidism and received thyroid hormone therapy. Hypothyroidism was not associated with increased risk of hospitalization [Adjusted Odds Ratio (ORadj): 1.23 (95% Confidence Interval (CI): 0.88- 1.70)], mechanical ventilation [ORadj: 1.17 (95% CI: 0.81–1.69)] nor death [ORadj: 1.07 (95% CI: 0.75–1.54)]. This study provides insight into the role of hypothyroidism on the outcomes of COVID-19 positive patients, indicating that no additional precautions or consultations are needed. However, future research into the potential complications of COVID-19 on the thyroid gland and function is warranted.